The Red Carpet: Bangalore Stories
Wry humor and a delicious grasp of the friction between generations in Bangalore are the hallmarks of Lavanya Sankaran\\\\\\\'s fresh, deeply nuanced debut collection. \\\\\\\A potpourri of beggars and billionaires and determinedly laid-back ways,\\\\\\\ Bangalore, India\\\\\\\'s own Silicon Valley, is a crucible for prosperity, and at the chaotic crossroads between past and present. Here, American-trained professionals like Tara return to their old-fashioned families with heads full of Quentin Tarantino dialogue; a successful entrepreneur is shaken when his partner suddenly reneges on their plan to return to America; a traditional Indian mother slyly circumvents her Western-educated daughter\\\\\\\'s resistance to marriage; a neighborhood gossip is determined to discover what goes on behind the closed curtains of the hip young couple across the street; a chauffeur must reconcile his more orthodox credos with his employer\\\\\\\'s miniskirt lifestyle.Witty, affectionate, and wonderfully wise, Lavanya Sankaran\\\\\\\'s first collection attests to her remarkable literary talent.